Transportation system management / Assoc. Prof. Hj. Zakaria Ahmad - Ahmad, Zakaria (Malaysia Institute of Transport (MITRANS), 2013)
A sustainable transportation system has been defined as one that satisfies current transport and mobility needs without compromising the ability of future generations to meet their own (Black, 1997; Richardson, 1999). Nowadays, number of students increase significantly; this has led to increase in ownership and use of the car to the point that UiTM; Shah Alam is facing a serious impact from car traffic and parking shortages. At the same time, that the car has had a major negative impact on the quality of life in campus communities. Moreover, as car use increases to ever higher levels, the car tends to drive out competing modes, thus limiting travel options. That is partly due to the car's genuine benefits, but also results from the negative impacts of car use of other modes. By introducing the green campus in terms of transportation initiative, it can help to improve transportation options and reduce trips at colleges, universities and other campus facilities. University campuses can constitute a laboratory for testing and implementing various alternative transportation strategies, reducing infrastructure costs and minimizing their impact on surrounding areas.